An initial lexicon of sensory properties for nail polish - Sun, Chen; Koppel, Kadri; Chambers, Edgar, IV (My University, 2014)
OBJECTIVE: The objective of this study was to develop an initial lexicon for sensory properties of nail polish and to validate this lexicon using a descriptive analysis study of selected samples. METHODS: Seventeen commercial products from four categories (regular, flake-containing, water-based and gel) were used in this study. Descriptive sensory analysis was conducted in this study to characterize and evaluate application and removal properties of these nail polishes. Data was then processed by Analysis of Variance (ANOVA), Principal Component Analysis (PCA) and Pearson’s Correlation Coefficient analysis to explore the differences among samples and attributes. RESULTS: A lexicon of twenty-one sensory attributes was developed to describe the application of nail polish. It included three initial texture attributes, thirteen initial appearance attributes and five aroma attributes. A lexicon of five attributes in five stages was developed to describe the removal of nail polish. The results from ANOVA and PCA showed that attributes in the lexicon separated the different product categories. CONCLUSION: The results of this study indicated that descriptive sensory analysis can be used to evaluate nail polish. The results of this study present scientists who are working on nail polish an additional tool to describe application and removal properties of nail polish.
Keywords: Nail polish; Sensory; Descriptive analysis; Nail physiology; Statistics; Colour cosmetics